2015
DOI: 10.3349/ymj.2015.56.3.793
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Women with Moyamoya Disease: Experiences at a Single Center in Korea

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution NonCommercial License (http://creativecommons.org/ licenses/by-nc/3.0) which permits unrestricted noncommercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Purpose: Moyamoya disease (MMD) occurs predominantly in Korean and Japanese women. The aim of this study was to investigate clinical features and pregnancy outcomes in women with MMD. Materials and Methods: We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…There are however reported cases of vaginal delivery, the majority performed with epidural anesthesia, and many are operative (assisted) deliveries (Table 1). 7,1116 No increase in risk of neurologic complications was noted in patients who underwent vaginal delivery in these case series.…”
Section: Discussionmentioning
confidence: 65%
“…There are however reported cases of vaginal delivery, the majority performed with epidural anesthesia, and many are operative (assisted) deliveries (Table 1). 7,1116 No increase in risk of neurologic complications was noted in patients who underwent vaginal delivery in these case series.…”
Section: Discussionmentioning
confidence: 65%
“…24 While many centers choose cesarean section as the default method of delivery, healthy vaginal births are certainly possible, with the caveat that pain management (often with an epidural catheter) and avoidance of hyperventilation are crucial. 25 Overall, for moyamoya patients already revascularized, > 95% of mothers with moyamoya disease have good neurological outcomes after pregnancies, with all delivered children reported healthy. 23 In contrast, those females who were newly diagnosed with moyamoya during pregnancy (typically with a new stroke or hemorrhage) typically presented after 24 weeks of gestation, with >10% maternal mortality and >20% fetal death.…”
Section: Surgical/dental Procedures/pregnancymentioning
confidence: 90%
“…To the best of our knowledge, the cases where mother had PIVH were reported by few authors like Tamizuddin et al [3], Mehrkens et al [8], Newman and Al-Memar [9], Jung et al [10], except the first, in other 3 cases the cause was known to be moyamoya disease. However in the first case it is of unknown etiology.…”
Section: Case Historymentioning
confidence: 98%
“…Jayakumar et al reported 70% mortality with pan ventricular blood [1,3]. However patients with PIVH of unknown cause have better prognosis than those with a documented mechanism of hemorrhage (secondary intraventricular hemorrhage) [1,10] and also in the absence of parenchymal damage prognosis appears to be good [13]. Various treatment options have been tried in PIVH with minimal success like direct or indirect cerebral revascularization surgery, external ventricular drainage or ventriculo-peritoneal shunt and recently intraventricular infusion of thrombolytic agents.…”
Section: Case Historymentioning
confidence: 99%